Placenta Accreta Spectrum Disorder: A Retrospective Study of 78 Cases - Raida Al-Wazzan; Luma Al-Najafi (Al-Anbar Medical Journal)
Background: Placenta accreta spectrum (PAS) disorder is a potentially near-miss life-threatening hemorrhagic obstetrical condition causing maternal complications and death. As there was no unique method recommended for the treatment of PAS all over the world until now, an analysis of the treatment of these cases in the study’s locality was needed.Objectives: To analyze the management of cases with a diagnosis of PAS and study the maternal outcome.Materials and Methods: A descriptive observational retrospective case series study included 78 consecutive pregnant women with a diagnosis of PAS who were managed at Al-Khanssa Teaching Hospital in Mosul/Iraq from  June 1st , 2017 to May 31st , 2020. The grade of PAS, time of diagnosis, treatment modalities, and complications were studied and analyzed.Results: In these 3 years, 78 patients met the diagnostic criteria of PAS. Overall, 21.8% of patients had an antenatal diagnosis and had a scheduled Caesarean section. About half of cases (48.72%) had placenta increta. In 33.33% of patients, preservation of the uterus after removal of the placenta with good hemostasis was  successful. Hysterectomy was needed in 66.67% of cases. Maternal complications were reported in 16.67% of cases, and fortunately, no maternal death was reported.Conclusion: In a limited resource clinical setting, hysterectomy and preservation of the uterus after removal of the placenta with a low threshold to hysterectomy were two methods appropriate to treat PAS cases. Both these methods were effective with low complications by  an experienced obstetrician.